Targeting ROR1 in combination with pemetrexed in malignant mesothelioma cells. (January 2020) - Miyake, Noriko; Ochi, Nobuaki; Yamane, Hiromichi; Fukazawa, Takuya; Ikeda, Tomoko; Yokota, Etsuko; Takeyama, Masami; Nakagawa, Nozomu; Nakanishi, Hidekazu; Kohara, Hiroyuki; Nagasaki, Yasunari; Kawahara, Tatsuyuki; et al.
Highlights: ROR1 appears to be a targetable molecule in malignant mesothelioma. ROR1 inhibition in malignant mesothelioma cells suppressed growth and colony formation. Thymidylate synthase was downregulated in mesothelioma cells transfected with siROR1. A combination of pemetrexed with siROR1 was effective in malignant mesothelioma cell lines. Abstract: Objective: Receptor tyrosine kinase-like orphan receptor 1 (ROR1) is overexpressed in a subset of malignant cells. However, it remains unknown whether ROR1 is targetable in malignant mesothelioma (MM). Therefore, in this study, we investigated the effects of ROR1 inhibition in mesothelioma cells. Materials and methods: Growth inhibition, colony formation, apoptosis, and mRNA/protein levels using siRNA-transfected MM cells were evaluated. Cluster analysis using Gene Expression Omnibus repository of transcriptomic information was also performed. Results: Our results indicated that in three (H2052, H2452, and MESO-1) among four MM cell lines, ROR1 inhibition had anti-proliferative and apoptotic effects and suppressed the activation of AKT and STAT3. Although growth inhibition by siROR1 was minimal in another mesothelioma cell line (H28), colony formation was significantly suppressed. Microarray, quantitative polymerase chain reaction, and Western blot analyses showed that there were differences in the suppression of mRNA and proteins between H2452 and H28 cells transfected with siROR1 compared with those transfected with control siRNA. Cluster analysis further showed that MM tumors had relatively high ROR1 expression, although the cluster in them was different from that in MM cell lines. Thymidylate synthase, a target of pemetrexed, was downregulated in H2452 cells transfected with siROR1. Accordingly, a combination of pemetrexed with siROR1 was found to be effective in the three MM cell lines we studied. Conclusion: Our findings may provide novel therapeutic insight into the treatment of advanced MM.